Edukasi dan Pendamping Petugas Dalam Meningkatkan Ketepatan Kodifikasi Diagnosis ICD-10 pada Karakter Keempat di Klinik Brimob Polda Kalimantan Selatan - Soraya Soraya; Hastin Atas Asih; A. Rasyid Ridha R; M. Heriyadi; Nadira Amelia Oktiana (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This community engagement activity aims to improve the knowledge and skills of officers at the Klinik Brimob Polda Kalimantan Selatan in accurately assigning ICD-10 diagnostic codes up to the fourth character. The main problem identified is the low accuracy of codification because officers frequently use three-character block codes due to habit and high workload. The implementation methods include comprehensive socialization, technical training using a hands-on practice approach, and direct mentoring and supervision. Evaluation was conducted through pre-test, post-test, and medical record audits. The results of the activity showed an increase in the competence of officers in assigning specific codes. Despite the high workload constraints, small group mentoring between service hours successfully overcame the challenges. In conclusion, education and continuous mentoring effectively improve the accuracy of ICD-10 codification up to the fourth character. The evaluation results demonstrated an increase in post-test scores among all participants from various health professions after receiving education and technical mentoring. This activity involved medical record officers, nurses, midwives, dental nurses, and doctors at Klinik Brimob Polda Kalimantan Selatan. Based on an audit of 150 post-training medical record documents, the accuracy rate of ICD-10 diagnosis codification up to the fourth character reached 83.3%, indicating an improvement in the precision and specificity of diagnostic code determination.